PENGARUH MODEL RADEC DENGAN METODE SUSTAINED SILENT READING (SSR) TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN - Novia Rahmawati; Arif Wiyat Purnanto; Agrissto Bintang Aji Pradana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of the RADEC (Read, Answer, Discuss, Explain and Create) learning model with the Sustained Silent Reading (SSR) Method on the Reading Comprehension Skills of Grade IV Students of MI Muhammadiyah Paremono Mungkid. Type of quasi-experimental research (Quasi Experimental Research). Sample selection using the Purposive Sampling technique. The sample of this study is all students of grades IVA and IVB of MI Muhammadiyah Paremono with 23 students in each class. Data collection instruments are in the form of tests and observations. The instrument is tested for validity by experts and tested with the help of SPSS Statistic 25 and its reliability test. Data analysis includes Shapiro Wilk normality test and Hypothesis Test using Paired Sample T-Test and Independent Sample T-Test assisted by SPSS Statistic 25. The results of the study showed that the RADEC (Read, Answer, Discuss, Explain and Create) model with the Sustained Silent Reading (SSR) Method on the Reading Comprehension Skills of Grade IV Students of MI Muhammadiyah Paremono Mungkid. This can be proven through the results of the analysis in the Paired Sample T-Test which produced a Sig.(2-tailed) of 0.000<0.05. The results showed that the average score of the pretest results was 50, increasing after the posttest the average score to 75.4. Therefore, the RADEC learning model with the Sustained Silent Reading (SSR) Method has a positive effect on Students' Reading Comprehension Skills.